Consumption of superplasticizer admixture for different cements and their binder efficiency - CECEL,R. T. (2019)
Abstract The optimum content of ether polycarboxylate-based superplasticizer, determined by rotational rheometry, and its effects on the environmental impacts of concretes were studied for cement and limestone filler. To assess the consistency and water reduction, flow-table tests were performed. Then, cement content reduction and binder and carbon intensity indexes were determined through estimation based on theoretical concretes. The evaluated pure and blended cements present significant variability of the optimum consumption of the admixture. The fillers consumed less superplasticizer per area than the other materials and compositions with fillers allowed for greater reduction of water content. The mixtures with superplasticizer presented lower cement rate and binder and carbon intensity indexes. The usage of this type of admixture in optimal content can reduce environment impacts, according to the parameters analyzed.